2016
DOI: 10.1136/bcr-2016-217790
|View full text |Cite
|
Sign up to set email alerts
|

Invasive group G streptococcal infection in a paediatric patient

Abstract: We present a paediatric case of group G streptococcal bacteraemia and vertebral osteomyelitis. The patient is a 14-year-old girl with Gaucher disease type 1 who presented with severe thoracolumbar pain. She was treated with a 4-week course of antibiotics for presumed osteomyelitis with clinical improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…This search strategy produced 14 total articles, with one relevant report (3). Removal of the filters produced two additional relevant reports (4,5). Web of Knowledge was searched with the same terms, producing 389 articles with two relevant reports not found on PubMed (6, 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This search strategy produced 14 total articles, with one relevant report (3). Removal of the filters produced two additional relevant reports (4,5). Web of Knowledge was searched with the same terms, producing 389 articles with two relevant reports not found on PubMed (6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…All but one child were previously healthy. A 14-year-old girl with vertebral osteomyelitis suffered from Gaucher's disease and had a prior history of osteomyelitis of the tibia (5). Five isolates were identified as GGS, while two were identified as Streptococcus dysgalactiae subspecies equisimilus.…”
Section: Discussionmentioning
confidence: 99%
“…The primary reason to treat this self-limited illness with antibiotics is to reduce the risk of complications such as rheumatic fever, meningitis, endocarditis and retropharyngeal abscess. [1][2][3] Antibiotic therapy also reduces the risk of suppurative complications of streptococcal infection. 4 A Cochrane review of randomised, placebo-controlled trials showed that antibiotic therapy significantly reduced the risks of acute otitis media and peritonsillar abscess.…”
Section: Descriptionmentioning
confidence: 99%